Influence features of office building rental: A systematic literature review / Muhamad Harussani Abdul Salam ... [ et al.] - Abdul Salam, Muhamad Harussani; Mohd, Thuraiya; Masrom, Suraya; Johari, Noraini; Mohamad Saraf, Mohamad Haizam (Universiti Teknologi MARA, Perak, 2022)
In reviewing rental trends, investors are unable to rely on market data from real estate transactions due to inaccurate property rental valuations by valuers. Hence the objective of this research which is to identify the influencing features of office building rentals. This study performs a systematic review on the influencing features of office building rentals based on the PRISMA systematic review and meta-analysis. The results obtained indicate that office rent determinants such as green labels, vacancy levels, and location-specifics, have significant impact on office rents. This paper provides new insights for investors and valuers in determining office rental values in the real estate market.